2018
DOI: 10.1111/tmi.13127
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis‐associated nephropathy in hospitalised Brazilian patients: new insights based on kidney injury biomarkers

Abstract: Visceral leishmaniasis-associated nephropathy showed important proximal tubular injury and glomerular inflammation. Serum NGAL showed an early association with VL-associated nephropathy and may be used to improve clinical management strategies and decrease morbimortality in VL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…and Plasmodium spp. In patients with visceral leishmaniasis (VL), Meneses et al [ 49 ] examined urine KIM-1 (uKIM-1). The mean uKIM-1 level was above 3 times higher in patients with VL and acute kidney injury (AKI group) compared to healthy patients, above 2 times higher in patients with VL and without acute kidney injury (non-AKI group) compared to healthy individuals, and almost 1.5 times higher in AKI group compared to the non-AKI group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Plasmodium spp. In patients with visceral leishmaniasis (VL), Meneses et al [ 49 ] examined urine KIM-1 (uKIM-1). The mean uKIM-1 level was above 3 times higher in patients with VL and acute kidney injury (AKI group) compared to healthy patients, above 2 times higher in patients with VL and without acute kidney injury (non-AKI group) compared to healthy individuals, and almost 1.5 times higher in AKI group compared to the non-AKI group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a higher expression of KIM-1 in the AKI group compared to the non-AKI and control group of patients. Meneses et al [ 49 ], van Wolfswinkel et al [ 50 ], and Punsawad and Viriyavejakul [ 51 ] suggested that KIM-1 is not a promising biomarker for early detection of nephropathy in visceral leishmaniasis and malaria. Contrary to the aforementioned studies, we suggest that KIM-1 can be considered for the early detection of renal acanthamoebiasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, understandings of kidney involvement are still limited. Clinical observation revealed acute kidney injury [ 3 ] and renal tubular dysfunction [ 4 ]. Pathologically, both glomerulonephritis [ 5 ] and interstitial nephritis [ 6 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of visceral Leishmaniasis reported clinical presentations of proximal tubular damage with alteration in low-molecule protein, glucose, and uric acid reabsorption [ 4 ]. Another leishmaniasis case series reported elevated kidney injury molecule-1, a proximal tubule injury biomarker [ 3 ]. The apical exposure to protein overload in proximal tubular cells might induce a proinflammatory phenotype, leading to injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, in a prospective study, we showed high levels of urinary MCP-1 and urinary oxidative stress in patients with visceral leishmaniasis who had normal serum creatinine, suggesting the presence of glomerular inflammation and incipient renal damage 22 . Another biomarker that seems to be reliable for the early detection of subclinical kidney injury in tropical diseases is NGAL, which had a good accuracy in a recent study from our group 68 .…”
Section: Use Of New Biomarkers In Tropical Diseasesmentioning
confidence: 94%